PENINGKATAN PRESTASI DAN MINAT BELAJAR IPS MELALUI PENERAPAN MODEL PEMBELAJARAN MONOLOG ROLE PLAYING FOR DISCUSSION PADA KELAS VIII E SMP NEGERI 1 KANDEMAN SEMESTER 1 TAHUN PELAJARAN 2016/2017 - Sambodo, Tri (Harmony, 2018)
This study aims to determine the learning model effect of the  Role Playing for Discussion Monologue learning model in improving student learning interest in social studies subjects. The results of student activity observation in cycle I NR = 49.5, cycle II NR = 67.6 increase 18.1%. Questionnaire results of interest of students in cycle I who chose the answer indicator A (very interested) 16 students or 7% cycle II who chose the indicator A 105 students or 50% increase 43%. On indicator B (interested,) who chooses B in the first cycle 95 students or 47% while in cycle II who chooses B 92 students or 43%, a decrease of 3%. On indicator C (less interested) there were 78 students or 37% who voted and in cycle II only 13 students or 6% chose, a decrease of 24%. In indicator D (not interested) in the first cycle there were 21 students or 10% chose while in cycle II there were no students who chose. KD evaluation results in cycle I NR = 74.43, cycle II NR = 77.86 an increase of 3.43%. From the results of the study it can be concluded that in learning model implementation of the Role Playing for Discussion Monologue learning model, can improve the achievement of student learning interests.   Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Monolog Role Playing for Discussion dalam meningkatkan minat belajar siswa terhadap mata pelajaran IPS. Hasil observasi keaktifan siswa pada siklus I NR = 49,5, siklus II NR = 67,6 peningkatan 18,1 %. Hasil angket minat siswa pada siklus I yang memilih jawaban  indikator A (sangat berminat) 16 siswa atau 7 %  siklus II yang memilih indikator A 105 siswa atau 50 % peningkatan 43 %. Pada indikator B(berminat,) yang memilih B pada siklus I 95 siswa atau 47 % sedang pada siklus II yang memilih B 92 siswa atau 43 %, penurunan 3 %. Pada indikator C (kurang berminat) ada 78 siswa atau  37 % yang memilih dan pada siklus II hanya 13 siwa atau 6 % yang memilih, penurunan 24 %. Pada indikator D (tidak berminat) pada siklus I ada 21 siswa atau 10 % yang memilih sedang pada siklus II tidak ada siswa yang memilih. Hasil evaluasi KD siklus I NR = 74,43, siklus II NR = 77,86 peningkatan 3,43 %.   Dari hasil penelitian dapat disimpulkan bahwa pelaksanaan model pembelajaran Monolog Role Playing for Discussion dapat meningkatkan prestasi minat belajar siswa.